Phases in development of an interactive mobile phone-based system to support self-management of hypertension - Hallberg, Inger (Dove Medical Press, 2014)
Hypertension is a significant risk factor for heart disease and stroke worldwide. Effective treatment regimens exist; however, treatment adherence rates are poor (30%–50%). Improving self-management may be a way to increase adherence to treatment. The purpose of this paper is to describe the phases in the development and preliminary evaluation of an interactive mobile phone-based system aimed at supporting patients in self-managing their hypertension. A person-centered and participatory framework emphasizing patient involvement was used. An interdisciplinary group of researchers, patients with hypertension, and health care professionals who were specialized in hypertension care designed and developed a set of questions and motivational messages for use in an interactive mobile phone-based system. Guided by the US Food and Drug Administration framework for the development of patient-reported outcome measures, the development and evaluation process comprised three major development phases (1, defining; 2, adjusting; 3, confirming the conceptual framework and delivery system) and two evaluation and refinement phases (4, collecting, analyzing, interpreting data; 5, evaluating the self-management system in clinical practice). Evaluation of new mobile health systems in a structured manner is important to understand how various factors affect the development process from both a technical and human perspective. Forthcoming analyses will evaluate the effectiveness and utility of the mobile phone-based system in supporting the self-management of hypertension.